Factors of public speaking anxiety (PSA) and strategies to mitigate PSA among postgraduate students of Malaysian public universities in online presentations / Noorfarida Filzah Mohd Sobri Paridaluddin, Zhang Jing and Chen Ruohan - Mohd Sobri Paridaluddin, Noorfarida Filzah; Zhang, Jing; Chen, Ruohan (Universiti Teknologi MARA, 2023)
This study aims to examine the contributing factors of public speaking anxiety (PSA) among international and Malaysian postgraduate students and to explore the strategies and influences of PSA on the students’ learning performances. Adopting Personal Report of Public Speaking Anxiety (PRPSA) and Foreign Language Communication Anxiety Scale (FLCAS), a qualitative research design was employed. Three postgraduate students were chosen according to a selective sampling method and interviewed using semi-structured interview protocol. The interview questions were adopted and customised to suit the online context as a situation specific setting. Results indicated that fear of negative evaluation and making errors along with peer pressure were among the main reasons for PSA. To cope, the students employed practicing and making comprehensive preparation to reduce PSA. The strategies were also identified to be unique according to the students’ causes of anxiety. It is also found that PSA had a significantly negative influence on some postgraduates’ online learning performances while having a moderate effect on some other postgraduates. This research is significant to figure out the causes of learners’ foreign language anxiety and the relationship between speaking anxiety and academic performance.